2011
DOI: 10.1021/ja2011109
|View full text |Cite
|
Sign up to set email alerts
|

Nine Enzymes Are Required for Assembly of the Pacidamycin Group of Peptidyl Nucleoside Antibiotics

Abstract: Pacidamycins are a family of uridyl peptide antibiotics that inhibit the translocase MraY, an essential enzyme in bacterial cell wall biosynthesis not yet clinically targeted. The pacidamycin structural skeleton contains a doubly inverted peptidyl chain with a β-peptide and a ureido linkage, and a 3’-deoxyuridine nucleoside attached to DABA3 of the peptidyl chain via an enamide linkage. Although the biosynthetic gene cluster for pacidamycins was identified recently, the assembly line of this group of peptidyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 16 publications
(23 reference statements)
1
72
0
Order By: Relevance
“…S2). We have previously shown that uridyl tetrapeptides with N-terminal m-Tyr tethered to the β-amino of DABA could be formed using the nine NRPS and associated enzymes PacDHIJLNOPW in vitro (9). No uridyl pentapeptide could be detected from those enzymatic reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). We have previously shown that uridyl tetrapeptides with N-terminal m-Tyr tethered to the β-amino of DABA could be formed using the nine NRPS and associated enzymes PacDHIJLNOPW in vitro (9). No uridyl pentapeptide could be detected from those enzymatic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatic analysis revealed the building blocks in pacidamycins are assembled using a nonribosomal peptide synthetase (NRPS) thiotemplate logic, whereas the encoded NRPS modules and domains are highly dissociated and predicted to work with each other in trans. We further characterized the functions of the separate NRPS protein domains in vitro to delineate catalytic steps for activation and insertion of each building block in the pacidamycin scaffold (8,9). We have shown that nine NRPS enzymes encoded by the producing organism S. coeruleorubidus, when heterologously expressed and purified from Escherichia coli, allowed reconstitution of the 5′-aminouridyl-tetrapeptide framework of the pacidamycin family (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cis-diol of uridine was protected as dimethylacetonide, 8 which was then O-alkylated using geranyl bromide in the presence of NaH to give 4. 9 Geranylation at the 5-position of ribose was confirmed by an HMBC correlation from H-12 to C-11.…”
Section: Resultsmentioning
confidence: 99%
“…Two new series of peptidyl-uridines whose structures are based upon mureidomycin A and tunicamycin have been synthesised as inhibitors of C. jejuni PglC, and selected compounds show IC50 values in the range 40-250 µM [35]. The biosynthetic pathway to both the pacidamycin [36][37][38] and caprazamycin [39] antibiotics has been elucidated, hence the use of biosynthetic engineering offers the possibility of generating modified uridyl peptide antibiotics via fermentation in the future. shown that mureidomycin A and liposidomycin B are both slow-binding inhibitors, while tunicamycin is a reversible inhibitor [40,41].…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 99%